14–3-3 eta (η) protein as a promising marker for rheumatoid arthritis: relation to joint damage and subclinical atherosclerosis - Sahar A. Elsayed; Doaa Adel; Mohammed Zaki; Eman A. M. Alkady (Egyptian Rheumatology and Rehabilitation)
Abstract Background Accelerated atherosclerosis is a common health insult in rheumatoid arthritis (RA) patients. Pro-inflammatory cytokines, endothelial dysfunction, and autoantibodies participate in the progression of RA-related atherosclerosis. Novel biomarkers may help early detection of subclinical atherosclerosis and represent new therapeutic targets. We aimed to assess serum 14–3-3 eta (η) protein in RA patients and to explore its relation to radiological joint damage and subclinical atherosclerosis after excluding traditional risk factors for atherosclerosis. Results The patients have increased serum 14–3-3 η protein and carotid intima-media thickness (CIMT) compared to the controls. The serum 14–3-3 η protein in our patients was positively correlated with age, disease duration, Larsen score, Rt-CIMT, Lt-CIMT, mean CIMT, C reactive protein (CRP), and Anti-citrullinated protein antibodies (ACPA). At a 31.05 ng/ml cut-off value, 14–3-3 η protein had 86.7% sensitivity and 84% specificity for RA. At a 45.7 ng/ml cut-off value, 14–3-3 η protein had 70.3% sensitivity and 79.2% specificity for the CIMT. Conclusion 14–3-3 η protein may be a valuable prognostic marker for RA. It positively correlates with the Larsen score and thus may serve as a marker for joint damage. In addition, it may be a promising marker reflecting subclinical atherosclerosis comorbidity in RA patients even without clinical signs of atherosclerosis, as it positively correlates with CIMT with high sensitivity and specificity.